Előreláthatósági klauzula a szerződések jogában - Csécsy, Andrea (Debreceni Jogi Műhely, 2009)
The essay is about the clause of foreseeability in connection with damages for breach of a contract. This seems to be a constant problem throughout the history of law how and when it is reasonably to limit the amount of damages in case of breach. The general principle of full compensation originates in the main purpose of private law, restoring the violated financial situation. At the same time in business relations it often happens that damages occurred as consequences of breach highly exceed the contractual interest of the party and generate indirect damages independent from the violator’s influence. This is considered to be the starting point of the dilemma about restricting the damages availably for compensation. Full compensation and its relation to breach of a contract occurred in the Hungarian jurisprudence many times. Miklós Világhy suggested the reconsideration of full compensation in contract law in 1971. Attila Harmathy also suggested the implementation of foreseeability clause in the rules of contract law as the ‘best possible way to treat business relations between the parties’. Due to the historic and social differences various forms of foreseeability are known in the legal systems. The study examines the development of foreseeability, its first codification in the French Napoleonic Code Civil, its application in the law of the USA and some significant sentences of English courts. The first application of foreseeability was in the infamous Hadley v. Baxendale case, in which an English court worked out the meaning of contemplation rules. In the case of Victoria Laundry Ld. v. Newman Industries Ld. (1949) the court defined the meaning of foreseeability. According to the sentence of the case damages are limited to those that were foreseeable for the party at the time of entering a contract. The study also analyzes the German model of restricting damages of breach. The German theory ensures the possibility of exoneration for the violator if the other party failed to give proper information about the unusual danger of breach in the particular case. If the entitled party acted intentionally, the German law accepts exoneration. The essay demonstrates the adequate causality conception of the German law. This theory states that an act can only be the probable cause if – due to the normal and reasonable procession – it is able to cause such consequence. In our opinion foreseeability gives a stricter and much better solution of restricting damages with a more objective measurement for the obliged party on how to calculate his behavior in a certain contractual relation. The amount of risk can be predicted if the rules of damages for breach are based on foreseeability rather than adequate causality. The new Hungarian Civil Code plans to establish objective liability in contract law. The only exoneration can be the successful reference to unavoidable external cause. Beside this stricter liability the new Civil Code also introduce the possibility of limitation in damages, the application of foreseeability clause. This seems to be a significant preference for the obliged party. As in the Hungarian legal history foreseeability clause was never used, it is an essential question how judicature will interpret the rule in practice. In our opinion for an adequate application of the new clause it is necessary to take a closer look at the United Nations Convention on the International Sale of Goods (CISG), the Principles of European Contract Law (PECL) and the interpretation in the American and English case law. This study tries to give some help for it.